CULTURAL LEARNING IN TEACHING ENGLISH - Giyatmi Giyatmi (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
Learning a language is not only about learning its language aspects and four Language skills but also about its culture. A new language cannot be achieved entirely unless the students have achieved the cultural context of that language. This articles discusses; relation of language and culture, culture in foreign language teaching, language teaching methods view on culture, applying culture in EFL/ESL classroom. Introducing culture is suggested to foreign language learners focusing more on communicative ability with the target language. Language and culture are closely related. Most of language teaching methods view that language and culture are inseparable. Introducing culture has an important role in EFL/ESL. It can reduce misunderstanding, culture shock, and stereotype. Cultural teaching must be integrated with four language skills in language learning. Cultural materials that are good in language learning are authentic text such as literature, newspapers, film, vlogging, table manner practice, proverbs, folklore and the native speakers.